2011
DOI: 10.1007/s10548-011-0189-7
|View full text |Cite
|
Sign up to set email alerts
|

EEG Microstates During Resting Represent Personality Differences

Abstract: We investigated the spontaneous brain electric activity of 13 skeptics and 16 believers in paranormal phenomena; they were university students assessed with a self-report scale about paranormal beliefs. 33-channel EEG recordings during no-task resting were processed as sequences of momentary potential distribution maps. Based on the maps at peak times of Global Field Power, the sequences were parsed into segments of quasi-stable potential distribution, the 'microstates'. The microstates were clustered into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 28 publications
0
64
0
Order By: Relevance
“…References not in the text: (Corradini and Persinger, 2014;Pipinis et al, 2017;Schlegel et al, 2012). …”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…References not in the text: (Corradini and Persinger, 2014;Pipinis et al, 2017;Schlegel et al, 2012). …”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Earlier studies point to the correspondence of individual microstates to particular classes of mentation by influencing how incoming information is processed and reacted to, and reported afterwards to some degree: Class A has been associated with abstract thoughts (Lehmann et al 1998;Lehmann et al 2010), activity within auditory areas (Britz et al 2010) and visualization (Milz et al 2016); Class B was associated with visual imagery-type activities (Britz et al 2010), verbalization (Milz et al 2016) and paranormal belief (Schlegel et al 2012). MRI-EEG coupled studies suggested that Class C stems from a network related to saliency, whereas Class D -from a dorsal attention network (Britz et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Research to date indicates that class A refers to abstraction, class B to concrete thought, class C to decreased attention with decreased excitation, while the interpretation of class D remains unclear. Their prevalence (mean duration, frequency of occurrence per second, percentage of occupied total analysis time) and sequence reflect different higher-order mental processes (Schlegel, Lehmann, Faber, Milz, & Gianotti, 2012). For the time being, microstates may be among the most promising notions when using EEG in neuroeducation, as they appear to be suited for the discovery of psychophysiological signatures of cognitive functions responsible for learning (for example, social learning, metacognitive regulation in problem solving, insight in problem solving, implicit and explicit learning, etc.).…”
Section: Resultsmentioning
confidence: 99%